(untitled) (Pragnya Sarathi, 2026)
Network interdiction has become a vital topic in operations research and optimization. It examines how networked systems can be intentionally disrupted or affected by unforeseen disturbances. This paper presents a comprehensive overview of robust maximum flow interdiction problems that seek to restrict the maximum amount of flow an adversary can route through a network under uncertainty in network parameters. Additionally, the paper discusses various modelling approaches and solution techniques applied to these problems, highlighting their computational challenges and outstanding possible directions for future research.